The Role of Operational Management in Improving Supply Chain Performance - Nursia; Dasa Febrianti (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2025)
The supply chain has become an important foundation in the company's operations in the era of globalization, supporting the entire business process from the procurement of raw materials to the delivery of products to consumers. This study aims to analyze the role of operational management in improving supply chain performance in medium-scale manufacturing companies. Operational management functions to manage the production process, inventory control, distribution, and efficient use of resources. In the context of supply chains, coordination between units and business partners is the key to the smooth flow of goods, information, and finance. This study uses a descriptive qualitative approach through case studies in manufacturing companies, with data collection techniques in the form of interviews, observations, and documentation studies. The results show that the implementation of good operational management contributes significantly to cost efficiency, delivery timeliness, and customer satisfaction. Therefore, operational management is an important element in shaping superior supply chain performance.